Synthesis, Spectroscopic, Electrochemical and Biological Studies of Co(II), Ni(II) and Cu(II) Complexes of 2-Hydroxybenzylidene-2'-hydroxyaniline - Mehatab Begum, F.R.; Jayamani, V.; Hemalatha, R. (Asian Journal of Chemistry, 2011)
In this work, large numbers of cyanide functional groups were introduced onto pectin by grafting with polyacrylonitrile. The graft copolymerization reactions were carried out under nitrogen atmosphere using ceric ammonium nitrate as an initiator. Evidence of grafting was obtained by comparing FTIR spectra of pectin and the graft copolymer as well as solubility characteristics of the products. The synthetic conditions were systematically optimized through studying the influential factors including temperature, concentration of the initiator, acrylonitrile monomer and pectin.